Designing A Solar Thermal Cylindrical Parabolic Trough Concentrator By Simulation. - Mahinder Singh, Balbir Singh; Sulaiman, Fauziah (2003)
The focus on renewable energy in Malaysia gained momentum with the active involvement of the government and the private sector. This move can potentially help in diversifying the country's energy options besides relying on oil, natural gas, coal and hydro power.